Sources of galicisms in Czech and Russian fortification terminology in the 18th century. The historical and political context of the issue - Artemov, Andrej (Slavia Centralis, 2022)
The paper presents the situation in the field of Fortification, which took place in the 18th century. Thanks to the active work of French engineers, fortification terminology throughout Europe was filled with numerous Galicianisms, which were adopted widely in all European languages. In the 18th century, fortresses were built or modernised, both in Russia and in the Czech lands. The text analyses the real possibilities for the process of taking over Galicianism in Slavic languages: Czech and Russian. The language situation in Russia and the Czech lands differed sharply. At the beginning of the 18th century, Russian contacted many European languages actively, but first with Dutch and German (the great influence of French begins here later). Russian adopted French fortification terminology, among other things, from translations made from other languages (for example, from Dutch). Gallicisms could have come into Czech through direct contact with the French environment (French officers in the service of the Habsburg monarchy, and otherwise).
Keywords: gallicisms; fortifications’ terminology; loanword; borrowing; Czech; Russian; 18th century